Distribution and genotypic diversity of Listeria monocytogenes strains isolated from humans and ruminants with common clinical and pathological phenotypes (neurolisterioses and abortions) (review) - T. Yu. Bespalova (Аграрная наука Евро-Северо-Востока, 2022)
Listeria (L.) monocytogenes is an intracellular food pathogen that causes listeriosis in mammals in the form of sporadic cases or large outbreaks with a high mortality rate among humans and domestic ruminants. The determination of the sequence type (ST) and the clonal complex (CC) by multilocus sequencing (MLST) and other methods in L. monocytogenes strains from different sources allowed us to establish the existence of strains with organ tropism and causing forms of listeriosis common to humans and ruminants. The purpose of the review was to generalize the available data on the distribution and genotypic diversity of L. monocytogenes strains isolated during neurolisteriosis and abortions, their adaptation in the environment to determine a possible link between listeriosis of ruminants and humans. In general, the analysis of the differential distribution of STs/CCs of L. monocytogenes associated with humans and ruminants showed their significant variation, as well as the predominance of CCs (CC1, CC2, CC4, CC6, CC7, CC8, CC14, CC29, CC37, etc.) common to the studied host groups. Neurolisterioses in humans are mainly associated with hypervirulent CC1, CC6, CC4, CC2, in ruminants - CC1 and CC4, as well as CC8-16 and CC412. A special association of ST1 (CC1) with human and bovine neurolisteriosis has been determined, indicating increased neurotropism of ST1. In small ruminants (goats, sheep), neurolisterioses are associated with various STs from phylogenetic lineages I and II. Most of L. monocytogenes strains isolated from abortions belonged to CC1, CC2, CC4, CC6, CC7, CC14 in humans and CC1, CC6, CC4-217, CC37 in ruminants. The detection of common isolates CC1, CC4-CC217, CC6, CC18, CC37 in ruminants and in their natural environment indicates that the farm environment is a reservoir for L. monocytogenes strains. In the Russian Federation, the prevalence of SТ7 isolates among all types of sources obtained on the territory of the country was noted. Future research should be aimed at studying the pathogenicity of L. monocytogenes strains with an increased tendency to cause diseases in humans and ruminants for better understanding the mechanisms of infection and strengthening the control over the spread of the pathogen in various ecological niches.